Spatial Modelling of Potential Fishing Zones For Narrow-Barred Spanish Mackerel (Scomberomorus commerson) in The Border Waters of Indonesia Timor Leste Based on Maximum Entropy Algorithm - Muhammad Habibi; Cinta Putri Maharani; Zaskia Dwiki Utami; Muhammad Roman Rihardi (Universitas Airlangga, 2026)
The narrow-barred Spanish mackerel (Scomberomorus commerson) is an important pelagic species in the waters along the Indonesia–Timor-Leste border. Fluctuations in oceanographic conditions often make it difficult for fishermen to determine efficient fishing locations. This study aims to identify Potential Fishing Zone (PFZ) for the December 2023 period by integrating Sea Surface Temperature (SST), Chlorophyll-a, and vessel track data. The methods employed include extracting Level 3 AQUA MODIS satellite data using SeaDAS, performing Inverse Distance Weighting (IDW) spatial interpolation analysis in ArcGIS Pro, and modeling habitat suitability probability using the Maximum Entropy (MaxEnt) algorithm. The analysis results indicate that in December 2023, the oceanographic conditions of the waters had an SST range of 27.36°C–32.40°C and chlorophyll-a levels of 0.073-1.503 mg/m³. Based on the calibration of 143 actual vessel presence points, the MaxEnt model produced good predictive performance with an Area Under the Curve (AUC) value of 0.7321. The Sea Surface Temperature (SST) parameter contributed dominantly at 93.7% to habitat suitability probability, while chlorophyll-a contributed 6.3%. The mapped Potential Fishing Zone (PFZ) is concentrated in the coastal transition zone. The results demonstrate spatial agreement between model predictions and actual fishing locations, which can serve as foundational marine geospatial information for fishermen to reduce search time and improve fleet operational efficiency.